PENGARUH BAGI HASIL TERHADAP KEPUTUSAN PENGGUNAAN JASA PERBANKAN SYARIAH TABUNGAN MUDHARABAH PADA PEGAWAI DI SEKOLAH MAN 2 KOTO BARU PADANG PANJANG - Bashir, Husnul; Taufiq, Muhammad (STAI Darul Qalam Tangerang, 2024)
This research is based on the fact that currently the general public requires banking services, especially as a place to store their income in the form of savings. Where is the financial management of the income earned for employees at the MAN 2 Koto Baru Padang Panjang School motivated to decide to become a customer in using mudharabah savings because there is profit sharing from this mudharabah contract from the use of services in Islamic banking. The purpose of this study is to measure the magnitude of the influence of profit sharing (X) on employee decisions (Y) in using mudharabah savings. This study used descriptive quantitative research with purposive sampling of 100 respondents. Respondents in this study were employees at the MAN 2 Koto Baru Padang Panjang School. The results of this study state that partially Profit Sharing has a positive and significant effect on the Decision to Use Mudharabah Savings Sharia Banking Services. This is evidenced by the value of t count is greater than t table (8.304> 1.984), and a significance value of 0.000 (sig <0.05). The influence of the Profit Sharing variable on employee decisions in using mudharabah savings banking services is 0.617, which means that if profit sharing increases by 1 percent, the decision to use mudharabah savings banking services increases by 61.7 percent. Then Profit Sharing is able to influence 41.3% change in the decision to use Islamic banking services, mudharabah savings